Using Internet Marketing and Social Media to Promote Ecotourism in Ukraine (Based on the Experience of Norway and Iceland) - Kniazieva, Tetiana V.; Kazanska, Olenа O.; Orochovska, Lyudmila A.; Horiunova, Kateryna A.; Chernyshova, Taia V. (Sport i Turystyka. Środkowoeuropejskie Czasopismo Naukowe, 2024)
Ecotourism is a type of sustainable tourism that has gained popularity in recent years. Its primary focus is preserving natural andcultural heritage and promoting responsible travel practices. Norway and Iceland have emerged as leading ecotourism destinations, offering breathtaking landscapes, diverse wildlife, and a solid commitment to sustainability. These countries have implemented successful ecotourism marketing campaigns that have attracted a significant number of sustainable travelers. On the other hand, Ukraine is still in the early stages of ecotourism development. However, recent efforts have been made to promote the country’s natural and cultural heritage as a potential ecotourism destination. The article reveals that with its vast natural resources and diverse cultural heritage, Ukraine has the potential to become a well-known ecotourism destination, contributing to the country’s economic growth while preserving its natural and cultural heritage. Thus, the authors’ objective is to analyze how the experience of countries with a developed ecotourism sector will help Ukraine promote this type of recreation on its territory. Ekoturystyka to rodzaj turystyki zrównoważonej, który zyskał popularność w ostatnich latach. Jej głównym celem jest ochrona dziedzictwa naturalnego i kulturowego oraz promowanie praktyk odpowiedzialnego podróżowania. Norwegia i Islandia stały się wiodącymi celami ekoturystyki, oferując zapierające dech w piersiach krajobrazy, różnorodną przyrodę i solidne zaangażowanie w zrównoważony rozwój. Kraje te wdrożyły udane kampanie marketingowe w zakresie ekoturystyki, które przyciągnęły znaczną liczbę osób podróżujących w sposób zrównoważony. Z drugiej strony Ukraina jest wciąż na wczesnym etapie rozwoju ekoturystyki. Jednakże ostatnio podjęto wysiłki w celu promowania dziedzictwa naturalnego i kulturowego tego kraju jako potencjalnego celu ekoturystyki. W artykule wykazano, że dzięki swoim ogromnym zasobom naturalnym i różnorodnemu dziedzictwu kulturowemu Ukraina ma potencjał, aby stać ...